Bilateral "Rescue Strip" Technique for Endoscopic Endonasal Approaches to the Clivus. Issue 2 (9th October 2020) - Kim, Matthew; Otten, Marc; Overdevest, Jonathan B; Gudis, David A
Abstract: BACKGROUND: The vascularized nasoseptal flap (NSF) is a pillar of contemporary endoscopic skull base reconstruction. The pedicle for the NSF is supplied by the posterior septal branch of the sphenopalatine artery, which courses along the arch of the choana and sphenoid rostrum before entering the nasal septum. Resection or mobilization of this region is necessary for surgical access to the clivus. OBJECTIVE: To describe a technique for preserving bilateral NSF pedicles during endoscopic endonasal resection of the clivus, thereby safeguarding availability of the flaps for future skull base repair needs. METHODS: Report of operative technique with video demonstration. RESULTS: This technique for NSF preservation allows for wide access to the clivus while saving the future option for vascularized flap repairs of skull base defects. The patient in whom we demonstrate this technique underwent complete resection of her clivus without cerebrospinal fluid leak and with preservation of both NSF pedicles. CONCLUSION: The "rescue strip" technique for endonasal endoscopic clival surgery preserves the bilateral NSF pedicles for future use without compromising surgical access to the clivus.